Housing politics in the United Kingdom : power, planning and protest / Brian Lund. - Lund, Brian, 1945- (Policy Press, 2016)
As housing moves up the UK political agenda, Brian Lund uses insights from public choice theory, the new institutionalism and social constructionism to explore the political processes involved in constructing and implementing housing policy and its political consequences.